ANALISIS KURIKULUM PENDIDIKAN LINGKUNGAN HIDUP PADA SEKOLAH DASAR PEKANBARU - Mahmud Alpusari (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2013)
The purpose of this research is that to create even distribution and understanding about life areaeducation to primary school students that will obtain students’ attitudes in doing actionsappropriating to the concept of life area education and create an alternative the development of lifearea education in Pekanbaru based on national curriculum or local curriculum. So that it can givecontribution to the curriculum in in real on the framework of life area education. The data used in thisresearch were primary and secondary data. Primary data sources from survey (direct observation) atschool, interview with stakeholder related to Head of Education Department, headmasters, andteachers. Primary data were also obtained by giving qutionare to headmasters, teachers, and studentsrelated to cognitive, affective, and psychomotor about life area education. Secondary data wereobtained from school condition like document of PLH activities at school and also stakeholders. Basedon the data of school curriculum analysis to life area education that it can be integrated into fivesubjects that are religion, civics, science and technology, art, and physic education. Based oneducation stakeholder analysis that they supported the life area education to put into local curriculumand to be implemented into daily life at school. Based on analysis data on knowledge and attitudesthan primary school students fully understood about life area education, and they have done to careabout school area.Key Words: curriculum analyze, life area education